Peranan Penanaman Modal Asing Sebagai Upaya Peningkatan Petumbuhan Ekonomi di Sumatera Selatan Menuju Sumatera Selatan Maju - Dea Justicia Ardha (Universitas Batanghari Jambi, 2021)
The economic development of a country, especially the developing country such as Indonesia and the regions in particular are largely determined by the growth rate of foreign investment. The social welfare of the community is strongly influenced by economic capacity to increase income fairly and evenly. The goverment of South Sumatera provinsial is also making efforts to attract investors, especially foreign investors to carry act in investment activities in South Sumatera, which as expected to have positive impact or development of the regional business in order to spur the growth of regional business, for example to advance the handicraft industry and micro, small and medium enterpires (MSME/UMKM) to increase people’s economy which will lead to increase and aqual distribution of people’s welfare in south sumatera towards andvanced South Sumatera.